Perancangan Antarmuka Website Company Profile dengan Menggunakan Goal-Directed Design - Pratama Putra, Raden Febrian Adjie; Perdanakusuma, Andi Reza; Syawli, Almira (JATISI, 2025)
Klinik Utama dr. Benggol was re-inaugurated recently with a new management team and services under “One-Stop Service” concept. This concept and re-inauguration gives the clinic a new identity as an integrated healthcare unit for the Ciliwung area. Various efforts were conducted to introduce the clinics new identity to the public, but the current website active website remains untouched and not showing changes happened within the clinic. This research aims to design a company profile website interface as a platform to deliver new services and information of the clinic. The Goal-Directed Design (GDD) method were used to systematically conduct the research. Starting with observation and interviews, persona creation, use case diagrams, user journeys, design and prototype testing based on scenarios and evaluation with the System Usability Scale method. The final prototype have overall great usability, shown by having efficiency score of 97,5%, effectiveness score of 95% and average SUS score of 77,5. Although there were several improvement suggested by the participant involved, the prototype can be used as a foundational instrument for developing a new website based on the clinic and it’s prospective users needs.